2009
DOI: 10.1101/gr.094060.109
|View full text |Cite
|
Sign up to set email alerts
|

Predictable dynamic program of timing of DNA replication in human cells

Abstract: The organization of mammalian DNA replication is poorly understood. We have produced high-resolution dynamic maps of the timing of replication in human erythroid, mesenchymal, and embryonic stem (ES) cells using TimEX, a method that relies on gaussian convolution of massive, highly redundant determinations of DNA copy-number variations during S phase to produce replication timing profiles. We first obtained timing maps of 3% of the genome using high-density oligonucleotide tiling arrays and then extended the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
135
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(167 citation statements)
references
References 33 publications
(42 reference statements)
23
135
4
Order By: Relevance
“…In our previous study , we have shown that the other half of the human genome is more in agreement with the dichotomic picture proposed in early studies of the mouse (Farkash-Amar et al 2008;Hiratani et al 2008Hiratani et al , 2010 and human (Desprat et al 2009;Ryba et al 2010;Yaffe et al 2010) genomes, where early and late replicating regions occur in separated compartments of open and close chromatin, respectively.…”
Section: Distribution Of Promoter Chromatin States Outside Replicatiosupporting
confidence: 70%
See 2 more Smart Citations
“…In our previous study , we have shown that the other half of the human genome is more in agreement with the dichotomic picture proposed in early studies of the mouse (Farkash-Amar et al 2008;Hiratani et al 2008Hiratani et al , 2010 and human (Desprat et al 2009;Ryba et al 2010;Yaffe et al 2010) genomes, where early and late replicating regions occur in separated compartments of open and close chromatin, respectively.…”
Section: Distribution Of Promoter Chromatin States Outside Replicatiosupporting
confidence: 70%
“…When mapping these chromatin states inside the megabase-sized U-domains Audit et al 2012Audit et al , 2013, where the MRT is U-shaped and its derivative Nshaped like the nucleotide compositional asymmetry in the germline skew N-domains (Brodie of Brodie et al 2005;Touchon et al 2005;Audit et al 2007;Huvet et al 2007;Audit et al 2009;Baker et al 2010;Chen et al 2011;, we have shown that in these replication domains that cover about 50% of the human genome, the replication wave ) proceeds along a directional path through the four chromatin states, from the open euchromatin state C1 at U/N-domain borders successively followed by the three silent chromatin states C2, C3 and C4 at the U/N-domain centers . The complete analysis, of the other half of the genome that is complementary to U-domains ) has confirmed the dichotomic picture proposed in early studies in mouse (Farkash-Amar et al 2008;Hiratani et al 2008Hiratani et al , 2010 and human (Desprat et al 2009;Ryba et al 2010;Yaffe et al 2010) genomes, where early and late replicating regions occur in separated compartments of open and closed chromatin, respectively. About 25% of the human genome is covered by megabase-sized GC-rich (C1 + C2) chromatin blocks that on average replicate early by multiple almost synchronous randomly positioned origins with almost equal proportions of forks coming from both directions which explains that the skew has not accumulated in these generich regions devoided of N-domains (Brodie of Brodie et al 2005;Touchon et al 2005;Baker et al 2010).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The generally lower intensity mid S pattern is also consistent with the possibility that many mid S loci are passively replicated by elongation from earlier initiation events ( Figure 8C). In this second model, there is also a potential for larger regions to be replicated by unidirectional forks, as has also been hypothesized for TTRs between early and late replicating domains of mammals (Farkash-Amar et al, 2008;Hiratani et al, 2008;Desprat et al, 2009). Our data do not distinguish between the two models, and it is possible that both scenarios occur in different regions of the maize genome.…”
Section: Models For Maize Dna Replication Timingmentioning
confidence: 42%
“…Replication in mid S phase has also been indirectly discussed in the context of timing transition regions (TTRs), which connect adjoining earlier and later constant timing regions in mammals (Hiratani et al, 2008;Desprat et al, 2009;Ryba et al, 2010). Some have hypothesized that these TTRs consist of unidirectional replication forks spreading from origins active earlier in S phase (Hiratani et al, 2008;Ryba et al, 2010), while others have argued that such regions contain origins activated in a "cascading" or "domino" pattern by earlier firing origins nearby (Guilbaud et al, 2011).…”
Section: Introductionmentioning
confidence: 99%